2005
DOI: 10.1016/j.jaci.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Lack of detectable allergenicity of transgenic maize and soya samples

Abstract: Background: The safety issues regarding foods derived from genetically modified (GM) plants are central to their acceptance into the food supply. The potential allergenicity of proteins newly introduced in GM foods is a major safety concern. Objective: We sought to monitor, in potentially sensitive human populations, the allergenicity effects of 5 GM materials obtained from sources with no allergenic potential and already under commercialization in the European Union. Methods: We have performed skin prick test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…One of the significiant examples of this is "StarLink" incident in USA.StarLink is the trading name of a genetically modified corn developed by Aventis Crop Science Company. This corn includes Cry9C protein and it is defined as "a potential alergenic" by US Environmental Protection Agency (EPA) so in 1998 EPA stated that StarLink can only be used as animal feed or in industry but it cannot be used as human food [34,35]. According to Ozdogan and Ekmen (2002) soyabean given Brazi-nut gene to enhance nutritional value caused severe allergic reaction and was prohibited in 1994 [36].…”
Section: Allergymentioning
confidence: 99%
“…One of the significiant examples of this is "StarLink" incident in USA.StarLink is the trading name of a genetically modified corn developed by Aventis Crop Science Company. This corn includes Cry9C protein and it is defined as "a potential alergenic" by US Environmental Protection Agency (EPA) so in 1998 EPA stated that StarLink can only be used as animal feed or in industry but it cannot be used as human food [34,35]. According to Ozdogan and Ekmen (2002) soyabean given Brazi-nut gene to enhance nutritional value caused severe allergic reaction and was prohibited in 1994 [36].…”
Section: Allergymentioning
confidence: 99%
“…Also, there have been associated allergic reactions to the consumption of modified soybean (Burks et al, 1988;Ogawa et al, 1993;Burks & Fuchs, 1995). Nevertheless Batiste et al in 2005, reported a study where volunteers did not showed allergic reaction after consumption of modified soybean and modified maize. Nevertheless, the benefits of the modified soybean exceed in much to the adverse effects.…”
Section: Risks Associated With the Transgenic Seedsmentioning
confidence: 99%
“…Thus, no significant level of IgE antibodies specific to the Cry1Ab protein could be found in the studied food-allergic patients. Batista et al (2005) performed skin prick tests with extracts of maize MON810 on children with food and inhalant allergy and individuals with asthma-rhinitis. None of the individuals undergoing tests reacted differently to the MON810 and the non-transgenic maize samples studied.…”
Section: Assessment Of Allergenicity Of the Whole Gm Plantmentioning
confidence: 99%